Bone marrow lesions in osteoarthritis: From basic science to clinical implications - Xiaorui Shi; Yiying Mai; Xiaofeng Fang; Zhiqiang Wang; Song Xue; Haowei Chen; Qin Dang; Xiaoshuai Wang; Su'an Tang; Changhai Ding; Zhaohua Zhu (Bone Reports, 2023)
Osteoarthritis (OA) is the most prevalent musculoskeletal disease characterized by multiple joint structure damages, including articular cartilage, subchondral bone and synovium, resulting in disability and economic burden. Bone marrow lesions (BMLs) are common and important magnetic resonance imaging (MRI) features in OA patients. Basic and clinical research on subchondral BMLs in the pathogenesis of OA has been a hotspot. New evidence shows that subchondral bone degeneration, including BML and angiogenesis, occurs not only at or after cartilage degeneration, but even earlier than cartilage degeneration. Although BMLs are recognized as important biomarkers for OA, their exact roles in the pathogenesis of OA are still unclear, and disputes about the clinical impact and treatment of BMLs remain. This review summarizes the current basic and clinical research progress of BMLs. We particularly focus on molecular pathways, cellular abnormalities and microenvironmental changes of subchondral bone that contributed to the formation of BMLs, and emphasize the crosstalk between subchondral bone and cartilage in OA development. Finally, potential therapeutic strategies targeting BMLs in OA are discussed, which provides novel strategies for OA treatment.